THE EFFECT OF SHOPEE PAYLATER ON STUDENT CONSUMPTION BEHAVIOR - Salamah, Ummu (Transpublika Publisher, 2022)
Globalization helps the globe to advance, particularly in the sphere of innovation, which is currently increasing rapidly as proven by the advent of Financial Technology (fintech), one of which is SPayLater. This study seeks to learn more on how teens, particularly students, use or engage in web-based buying using the spotlight of SPayLater. A subjective enlightening research strategy with a phenomenological perspective is used in this work. The review's findings are derived from a study of previous investigations. The findings indicate that the way of life or utilization and social impacts affect the use of SPayLater and, as a result, the shopping behavior of students for people who, in general, will like to shop with SpayLater making their lifestyle more luxurious, and the use of SPayLater due to social impacts ranging from mentors and promotions.